Analisis Faktor-Faktor Yang Mempengaruhi Konsumsi Daging Ayam Ras Di Kecamatan Teluk Ambon Kota Ambon - M J Matatula; A Kewilaa (PETERPAN (Jurnal Peternakan Terapan), 2023)
Increasing people's welfare is in line with increasing consumption of broiler meat as a source of animal protein. Improving a person's quality of life has implications for a selective attitude in choosing the quality and quantity of food consumed. This study aims to analyze the factors that influence the consumption of purebred chicken in Teluk Ambon District. The research location was determined purposively, namely deliberately in the market located in Teluk Ambon District, namely Pasar Rumah Tiga and Pasar Wayame. The basis for location considerations is that the people around the market have varied occupational professions and have heterogeneous levels of education. The research sample was drawn using the accidental sampling method, namely taking samples of respondents who are consumers who happen to shop for chicken meat. Respondents were taken as many as 60 people. To analyze the factors that influence the amount of consumption of chicken meat analyzed using multiple linear regression analysis method. The research results show that the price of chicken meat, the price of chicken eggs, the price of fish, the level of education, dependants, tastes, and income together have a significant influence on the amount of consumption of chicken meat. Partially, the variable price of chicken meat, the number of family dependents, income tastes have a significant effect on the amount of chicken meat consumption, while the price of chicken eggs, the price of fish, and the level of education have no significant effect on the amount of chicken meat consumption.